2017
DOI: 10.1002/oby.21871
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 4 mediates fat, sugar, and umami taste preference and food intake and body weight regulation

Abstract: Objective Immune and inflammatory pathways play important roles in the pathogenesis of metabolic disorders. In the present study we investigate the role of TLR4 in orosensory detection of dietary lipids and sugars. Methods Taste preferences of TLR4 knockout (KO) and wild type (WT) male mice under standard, and high fat and high sugar diets were assessed with 2-bottle tests. Gene expression of taste signaling molecules was analyzed in the tongue epithelium The role of TLR4 in food intake, and weigh gain was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
1
30
0
4
Order By: Relevance
“…Analysis of CD36 in human papillae immediately before and after consumption of dietary fat is necessary to confirm this. Some studies have also shown association between CD36 and hedonic preference for fatty foods in humans (13) and rodents (26)(27)(28)(29) , which strengthens the argument that the role of CD36 is more specific to mediating fat intake within a given meal. There is also evidence of interaction between FFAR4 and CD36 in TBC (30) , though the significance of this interaction remains unclear.…”
Section: Discussionmentioning
confidence: 60%
“…Analysis of CD36 in human papillae immediately before and after consumption of dietary fat is necessary to confirm this. Some studies have also shown association between CD36 and hedonic preference for fatty foods in humans (13) and rodents (26)(27)(28)(29) , which strengthens the argument that the role of CD36 is more specific to mediating fat intake within a given meal. There is also evidence of interaction between FFAR4 and CD36 in TBC (30) , though the significance of this interaction remains unclear.…”
Section: Discussionmentioning
confidence: 60%
“…In this context, it is interesting that Asano et al (2016) previously reported no significant association between oral fat sensitivity and the degree of greasy food preference in healthy young adults. For example, with respect to other genes, altered calorie-dense food preferences induced by gene mutations in the fat mass and obesity-associated (FTO) gene and Tolllike receptor 4 (TLR4, which encodes a transmembrane protein that belongs to the Toll-like receptor family) gene have been reported in humans and mice, respectively (Brunkwall et al 2013;Camandola and Mattson 2017). In these reports, it was suggested that the FTO polymorphism (reference SNP number: rs9939609; hypothalamic FTO is associated with the regulation of energy intake) and the deletion of TLR4 might be associated with altered hypothalamus function (a center that mediates food intake in the brain) and the altered expression of proteins in the tongue epithelium that are related to taste perception (including sweet, umami, and fat tastes), respectively.…”
Section: Fig 2 Comparison Of Basic Taste Preference Degrees Betweenmentioning
confidence: 99%
“…Прием пищи является одним из основных путей проникновения патогена, поэтому неудивительно, что многие компоненты иммунной системы экспрессируются в эпителии языка. В последние годы появляется все больше сообщений о функции компонентов врожденного иммунитета, не связанных с иммунологическим надзором [11,35]. В частности, к таким функциям относится и участие в восприятии вкуса.…”
Section: рисунок 2 сигнальный путь T2r [22]unclassified
“…В настоящее время стало известно, что лица, страдающие ожирением, сахарным диабетом 2-го типа и другими метаболическими расстройствами, имеют повышенные уровни экспрессии TLR4 в различных тканях. Это способствовало созданию идеи о том, что экспрессия TLR4 может влиять и на особенности восприятия вкуса, формируя пристрастия к определенной диете [35,39].…”
Section: рисунок 2 сигнальный путь T2r [22]unclassified
See 1 more Smart Citation